The analysis of methods for calculating seals of hybrid power machines - E. A. Pavlyuchenko; A. S. Tegzhanov; V. E. Shcherba; E. A. Lysenko; A. K. Kuzhbanov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses the main methods for calculating seals of hybrid power machines. The analysis of works on the designs of hybrid power machines is carried out. The main types of piston seals of pumps, compressors and hybrid power machines are considered, with an emphasis on the main advantages and disadvantages of each type of seal, as well as recommendations on the choice of seals for hybrid power machines. Based on the analysis of the work on the research of piston seals, the main methods for calculating the seals of hybrid power machines are considered and the most suitable one is determined.